EXAMPLE OF GOOD TEACHING PRACTICE - ENGLISH LANGUAGE TEACHING USING THE CLIL METHOD (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
The aim of this paper is to present one of the ways to conduct English language classes using the CLIL method. Such, rather innovative, integrated learning of language and content increases students' motivation, improves understanding and adoption of new concepts in the target language. In addition, CLIL teaching is an excellent introduction to bilingual teaching, which is a symbol of modern and promising education. Here, English is used as a tool for adopting mathematical terms, and not as a subject in itself. The class is easily applicable in school practice and has the function of interdisciplinary connection. The class was realized in January 2018 in the class of the 6th grade of the Elementary School "Dimitrije Tucović" in Kraljevo.